Butterfly cartilage graft myringoplasty results - Apuhan, Tayfun; Kaya, Mehmet Onur; Şimşek, Tuğçe; Kazaz, Hasan (Bolu Abant İzzet Baysal Üniversitesi, 2012)
OBJECTIVE: The aim of this study was to study a retrospective analysis of the cartilage graft butterfly myringoplasty performed by the Otolaryngology Head and Neck Surgery department.METHODS: Twenty-two subjects 26 ears were enrolled in the study. Surgery was performed under general anesthetic in 18 of the 26 ears and under local anesthetic for the remaining eight ears. In four subjects, surgery was performed on both ears as described by Eavey. Before the surgery and during the one postoperative year, an audiologist performed pure-tone audiograms. These audiograms were analysed retrospectively.RESULTS: Twenty-two subjects 26 perforated ears who ranged in age from 12 to 44 years were enrolled in this study. All 26 perforations treated by CGBM cartilage graft butterfly myringoplasty were successfully closed at the end of the follow-up period. The mean preoperative ABG for all 22 patients was 14,81±4,12 dB and postoperative 6,27±4,50 dB. The ABG of the cases were evaluated as having a statistically significant reduction in the mean postoperative ABG p

AMAÇ: Bu çalışmanın amacı Kulak Burun Boğaz Kliniğine başvuran ve “kıkırdak greft butterfly miringoplasti” ameliyatı yaptığımız kronik otitis medialı hastalarda işitme düzeyini retrospektif olarak analiz etmektir.YÖNTEMLER: Çalışmaya 22 hasta 26 kulak dahil edildi. 18 hastada genel anestezi altında 8 hastada lokal anestezi altında, gerçekleştirildi. Cerrahi 22 hastada tek kulakta 4 hastada her ki kulakta ve Eavey tarafından tarif edildiği şekilde gerçekleştirildi. Ameliyat öncesi ve ameliyat sonrası yapılan odyolojik incelemeler retrospektif olarak analiz edildi.BULGULAR: Çalışmaya dahil edilen 22 hasta 26 kulak ’ nın yaşları 12-44 arasında idi. Postoperatif takipte kıkırdak greft butterfly tekniği uygulanan 26 kulağın perforasyonunun kapandığı görüldü. Hastaların odyolojik incelemesinde ameliyat öncesi hava kemik aralığı ABG ortalama 14,81±4,12 dB iken, ameliyat sonrası ortalama 6,27±4,50 dB olarak ölçüldü. ABG acısından preoperatif döneme göre postoperatif dönemdeki azalmanın istatistiksel olarak anlamlı olduğu görüldü p
Butterfly kıkırdak greft miringoplasti sonuçları